Ileal intussusception due to primary intestinal melanoma with generalized lymph node metastases- a rare cause of small bowel obstruction - Rajendharan, Keerthi Andi; Balakrishnan, Gurushankari; Sundaramurthi, Sudharsanan; Krishnaraj, Balamourougan; Sistla, Sarath Chandra (International Surgery Journal, 2021)
Primary melanomas of small intestine are rare and most of them are metastases from cutaneous melanoma. The features distinguishing primary from metastatic intestinal melanoma are still under debate. Primary intestinal melanoma (PIM) is associated with a worse prognosis and a more aggressive behaviour due to its rapid growth. Hence, we report a case of primary ileal melanoma presenting as intussusception with generalized lymph node metastasis. A 69-year-old lady presented with recurrent abdominal pain, vomiting, distension and low grade fever. On examination, a 4*4 cm right inguinal lymph node was noted with no abnormalities on abdominal and per rectal examination. Computed tomography (CT) revealed ileoileal intussusception which was confirmed on laparotomy and diagnosed as primary ileal melanoma on histopathological examination (HPE). Whole-body Positron Emission Tomography (PET) CT revealed metastasis to lymph nodes all over the body. Intestinal melanomas are rare and mostly occur secondary to primary cutaneous melanoma. The clinical picture of intestinal melanoma is varied, ranging from chronic vague symptoms to surgical emergency such obstruction and bleeding. Treatment of both primary as well as metastatic intestinal melanoma is surgical excision. Intestinal melanoma, in general, carries a bad prognosis than cutaneous melanoma. Owing to the rarity and vague presentation, early diagnosis of intestinal melanoma requires a high index of suspicion, multimodal imaging and timely surgical intervention with adequate resection margins.